Enhanced Erythromycin Elimination from Erythromycin Fermentation Residue via Anaerobic Volatile Fatty Acid Production Under Mesophilic Conditions - Jianjun Ren; Xilong Xia; Honggang Mao; Lixia Zhu; Mohammad J. Taherzadeh; Yiliang Chen; Dongze Niu; Chunyu Li; Rui Tang; Xiancheng Qi; Chuanyang Xu; Dongmin Yin (Fermentation, 2025)
Erythromycin fermentation residue (EFR) is difficult to dispose of due to its high content of macrolide erythromycin. An alternative economic method was proposed in this study for erythromycin elimination in EFR through volatile fatty acid (VFA) production via an anaerobic digestion process. Different parameters were applied to evaluate the effects on energy recovery of VFA together with erythromycin elimination from EFR through batch assays under mesophilic conditions. Results demonstrated that anaerobic digestion technology for VFA production can significantly enhance erythromycin elimination in EFR. The highest removal efficiency of 86.7–87.5% was obtained at conditions of controlled pH at 11.0, with erythromycin decreasing from an initial 100.2 to 12.6–14.0 mg/L. Additionally, controlled pH during the digestion process was reported to positively improve VFA yield to a maximum of 1.04 g-COD/g-VS than the adjustment of initial pH (0.46 g-COD/g-VS). Metabolic analysis alongside high-throughput sequence analysis further demonstrated the high hydrolysis and acidogenesis activities of EFR during the VFA accumulation process. Dominate enzymes EC:3.2.1.40, EC:6.2.1.3, EC:4.1.2.14, EC:2.7.2.1, and EC:1.1.1.27 well balanced the whole process from organic to VFA at pH controlled 11.0. The current study provided a new feasible choice for the economical treatment of antibiotic fermentation residues due to the tolerable antibiotic removal efficiency and satisfactory VFA yield.